2018
DOI: 10.1002/joc.5673
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation changes in the Qilian Mountains associated with the shifts of regional atmospheric water vapour during 1960–2014

Abstract: Precipitation plays an essential role in hydrological cycle, water resource availability, and ecological economics sustainable development both within the Qilian Mountains (QM) and its surrounding. On the basis of meteorological station records and reanalysis data sets, we investigate the variations of precipitation in the QM during 1960-2014 and their connection to the shifts of regional atmospheric water vapour. Results show that precipitation in the QM as a whole has experienced pronounced wetting at an ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The variation of precipitation efficiency is related to the dominant midlatitude westerly regime, seasonal monsoon settlement in the lower atmosphere, and the blocking effect of topography. Precipitation during the summertime in upper HRB is mainly related to the ascent of monsoonal moisture from southeast China by prevailing East Asian Monsoon (Chen et al, ; Li et al, ; Wang et al, ; Wang, Pang, et al, ). This effect is also revealed by the spatial pattern of tagged precipitation, as more tagged precipitation falls at the high mountain peaks around northwestern part of the upper HRB in comparison to the southeastern part and valley area (Figure a), resulting in higher tagged precipitation recycling in the northwest part of upper HRB (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The variation of precipitation efficiency is related to the dominant midlatitude westerly regime, seasonal monsoon settlement in the lower atmosphere, and the blocking effect of topography. Precipitation during the summertime in upper HRB is mainly related to the ascent of monsoonal moisture from southeast China by prevailing East Asian Monsoon (Chen et al, ; Li et al, ; Wang et al, ; Wang, Pang, et al, ). This effect is also revealed by the spatial pattern of tagged precipitation, as more tagged precipitation falls at the high mountain peaks around northwestern part of the upper HRB in comparison to the southeastern part and valley area (Figure a), resulting in higher tagged precipitation recycling in the northwest part of upper HRB (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…A rise in tropospheric water vapour may result in increases in both the frequency and intensity of heavy precipitation (Mishra and Liu, 2014). It is reported that F I G U R E 1 Difference in the integrated precipitable water (IPW) (kgÁm -2 ) from 1980-1998to 1999-2018(IPW 1999-2018-IPW 1980-1998 ) from Modern Era Retrospective-Analysis for Research and Application (MERRA 2) model reanalysis tropospheric warming can increase the availability of atmospheric water vapour.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al . () linked the changes in precipitation patterns with shifts in regional atmospheric water vapour. Increased atmospheric water vapour over various parts of the globe shows large variability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the lateral flow was found to have a more pronounced enhancement of summer precipitation in West Africa than in Europe (Arnault et al, 2021), since West Africa is considered as a hot spot of soil moisture‐atmosphere coupling (e.g., Koster et al, 2004). Being characterized by a semiarid‐arid environment and high mountain terrain, our study area is not placed within the hot spots of land‐atmosphere coupling (Koster et al, 2004), meanwhile, studies have shown that local precipitation is mainly modulated by remote atmospheric water transport (e.g., Wang, et al, 2018; Zhang et al, 2021). For this reason, representing lateral flow in the WRF model does not considerably change or degrade the model performance of simulated meteorological variables and energy fluxes at a diurnal scale over the study area.…”
Section: Discussionmentioning
confidence: 99%